CHANGE IN THE MECHANICAL PROPERTIES AND STRESS CORROSION CRACKING UNDER MATERIAL OF METALWARE TENSION OF A CLAMP-FORMING MACHINE ARROW - Polishchuk, L. K.; Iskovych-Lototskyi, R. D.; Koval, O. O. (Science and Transport Progress, 2015)
Purpose. The aim is to study the effects of conditions and duration of working of structures arrows of a clamp-forming machine on mechanical properties of the material and its stress corrosion cracking under tension. It is necessary to improve the accuracy of resources analysis of boom metalwares of lifting and transporting machines. Methodology. Samples for experimental investigations were made of the elements of arrow continued exploited clamp-forming machine where there were major work stress. Centers of greatest efforts in elements of arrows constructions were determined in its 3D model in the analysis of the stress cards by finite element method. Experimental studies were performed at the facility UVP-6, which determined the characteristics of strength and ductility of samples of two types by means of tensile strain, speed 10-5 s-1 and 10-6 s-1 in air and in the environment of synthetic rain. Metallographic studies were performed on a scanning electron microscope. Findings. Experimental studies found that after long-term operation of arrow of clamp-forming machine material of its most loaded elements changed due to characteristics of strength and ductility. At joint action of corrosion environment and the greatest stress on the surface of the material expressions, point defects are appeared. They are concentrators of local mechanical stress, which reduce the resource construction elements of the arrow. Originality. 1) firstly set patterns of changes in the mechanical properties of continued operated metal construction of arrow of clamp-forming machine made of St. 3; 2) received further developed methodology for remaining resource estimation continued operated of metal boom lifting and shipping the machine by taking into account joint action vibration and dynamic loads and corrosive environments. Practical value. Determination the residual resource of continued operated boom lifting and transporting metal machines should be carried out taking into account the degradation of the mechanical properties of the material as well as the dynamic nature of the load. The obtained regularities on changes of mechanical properties and stress corrosion cracking under tension of an arrow material will contribute to increase evaluation accuracy of fragility of residual resource of load carrying steel structures.